Ocupación De Los Egresados Del Programa De Licenciatura En Educación Física Y Deportes De La Universidad Del Quindío (2014)
The different occupations of the graduates of the degree program in Physical Education and Sports of the University of Quindío were examined, in which was found a population of 184 people graduated from the program, which involved 102 graduates between men and women, teachers of level Middle, and high school students and program students. This allowed him to gather information by accessing his analysis, which allowed him to elucidate the realities of the Physical Educator. The survey used to collect the information was carried out and approved by the Board of Directors of the University of Quindío, the research was carried out in a quantitative way with an explanatory scope, which allows progress in self - evaluation processes to achieve improvement and strengthening of the Program. The information gathered shows the behavior of the graduates in the labor field, corresponding to the production of knowledge, to the private or public companies in which the graduates are linked, highlighting the positions and types of postgraduate studies that have been carried out By the professionals in the area of ​​Physical Education. Acceding to a reality that is present in the region, leading both students and graduates to work and focus on the educational issues of the Quindíana region.